Dairy value chains during the COVID-19 pandemic in Ethiopia: Evidence from cascading value chain surveys before and during the pandemic - Hirvonen, Kalle; Habte, Yetmwork; Mohammed, Belay; Tamru, Seneshaw; Abate, Gashaw T.; Minten, Bart (International Food Policy Research Institute, 2021)
We combine in-person survey data collected in February 2018 with phone survey data collected in June and September 2021 to study how dairy value chains in Ethiopia have coped with the COVID-19 pandemic. Focusing on the major dairy value chain connecting farmers in North and West Shewa as well as peri-urban and urban producers in and around Addis Ababa to consumers in Addis Ababa, we applied a cascading survey approach in which we collected data at all levels of the value chain: dairy farmers, rural wholesalers, and urban retailers.